A New Class of P(VdF-HFP)-CeO2-LiClO4-Based Composite Microporous Membrane Electrolytes for Li-Ion Batteries. (29th May 2011) - Vijayakumar, G.; Karthick, S. N.; Subramania, A.
Abstract : Composite microporous membranes based on Poly (vinylidene fluoride– co -hexafluoro propylene) P(VdF- co -HFP)-CeO2 were prepared by phase inversion and preferential polymer dissolution process. It was then immersed in 1M LiClO4 -EC/DMC (v/v = 1 : 1 ) electrolyte solution to obtain their corresponding composite microporous membrane electrolytes. For comparison, composite membrane electrolytes were also prepared by conventional phase inversion method. The surface morphology of composite membranes obtained by both methods was examined by FE-SEM analysis, and their thermal behaviour was investigated by DSC analysis. It was observed that the preferential polymer dissolution composite membrane electrolytes (PDCMEs) had better properties, such as higher porosity, electrolyte uptake (216 wt%), ionic conductivity (3.84 mS·cm −1 ) and good electrochemical stability (4.9 V), than the phase inversion composite membrane electrolytes (PICMEs). As a result, a cell fabricated with PDCME in between mesocarbon microbead (MCMB) anode and LiCoO2 cathode had better cycling performance than a cell fabricated with PICME.